Nairobi Impact Story: Pathways for risk-informed informal - Comelli, Thaisa; Pelling, Mark; Sinclair, Hugh; Esperancinha, Sérgio; Wilton, Ciara (UKRI GCRF Urban Disaster Risk Hub, 2024)
Since the inception of Tomorrow's Cities, many cities of the Global South have embarked on an innovative journey towards inclusive, participatory, risk informed urban planning and disaster risk management. These impact stories capture the unique pathways each city has taken—highlighting the strategies they adopted, the tangible changes they achieved, and the unforeseen opportunities that arose. Each narrative explores how local actions, driven by shared learning and collaboration, are paving the way for a safer and more inclusive urban future, and understand the potential for lasting impact in each city.
Keywords: Tomorrow's Cities Decision Support Environment; Disaster Risk Management; Inclusivity; Participatory; Risk Informed Urban Planning; Impact; Shared Learning and Collaboration; Future Visioning